A case of coronary venous angioplasty to facilitate left ventricular lead placement - Timmer, Stefan A. J. (Clin Case Rep, 2018)
Coronary venous stenosis is an uncommon finding in patients referred for cardiac resynchronization therapy device implantation. Nonetheless, it may result in suboptimal lead positioning for chronic left ventricular (LV) pacing. Coronary venous angioplasty is a technique that can be performed relatively easily and safely to enable LV lead passage beyond a stenosis.